2018
DOI: 10.4025/actascihealthsci.v40i1.33469
|View full text |Cite
|
Sign up to set email alerts
|

<b>Cardiac autonomic profile in cervical spinal cord injury subjects practitioners of the physical exercise

Abstract: The aim was investigate the time-course of cardiac autonomic response in men with incomplete cervical spinal cord injury (SCI) practitioners or not of physical exercise. Twenty men were separated into three groups: control group without SCI (CON; 28.3 ± 4.5 yrs; 178.4 ± 6.5 cm; 82.1 ± 6.8 kg; n=8), regularly engaged in strength training and low aerobic training; exercise group with cervical SCI (EG, 32.3 ± 4.5 yrs, 175.1 ± 5.3 cm, 73.6 ± 9.6 Kg; n=8) that practiced wheelchair rugby and sedentary group with cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In the present and previous studies, HRV alterations (particularly lower SDNN) were predictive of progressive coronary artery disease in people with SCI and were found more frequently in those with a sedentary lifestyle and without regular physical exercise[ 14 ]. Physical exercise after SCI is shown to increase sympathetic activity and may help minimize the risk of cardiac arrhythmias and prevent sudden cardiac death in those with cervical SCI[ 28 ]. Fatigue is also associated with altered HRV parameters and greater risk of cardiovascular sequelae after SCI; appropriate levels of exercise as well as sufficient sleep and dietary measures are recommended as anti-fatigue and anti–cardiovascular-risk strategies[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present and previous studies, HRV alterations (particularly lower SDNN) were predictive of progressive coronary artery disease in people with SCI and were found more frequently in those with a sedentary lifestyle and without regular physical exercise[ 14 ]. Physical exercise after SCI is shown to increase sympathetic activity and may help minimize the risk of cardiac arrhythmias and prevent sudden cardiac death in those with cervical SCI[ 28 ]. Fatigue is also associated with altered HRV parameters and greater risk of cardiovascular sequelae after SCI; appropriate levels of exercise as well as sufficient sleep and dietary measures are recommended as anti-fatigue and anti–cardiovascular-risk strategies[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present pilot study found that comprehensive evaluation of HRV and vascular age indicators addresses the full spectrum of poor AE, SDNN, and RMSSD in those with SCI. Studies have shown that physical activity, painting, respiratory training, music therapy, and nature therapy have the potential to reduce stress and improve HRV-related disorders and blood vessel structure[ 28 , 31 - 34 ]. Changes in the autonomic system, for example, are readily observed in response to physical exercise in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation